2
$\begingroup$

Let $p_n$ denote the $n$-th prime number . Let $r(n,k):=\dfrac {p_n...p_{n+k}}{p^k_{n+k+1}} , \forall n,k \in \mathbb N$ . I can show that for every $k \in \mathbb N , \exists n_k\in \mathbb N$ such that $r(n,k)>1 , \forall n>n_k$ .

My question is : Is it true that $\lim_{n\to \infty} r(n,k)=\infty , \forall k \in \mathbb N$ ?

If the limit doesn't exist , then is $\lim \sup _{n\to \infty} r(n,k)=\infty , \forall k \in \mathbb N$ ?

$\endgroup$
  • $\begingroup$ You have k+1 terms in the numerator and k terms in the denominator. Is that what you want? $\endgroup$ – marty cohen Oct 14 '17 at 21:04
2
$\begingroup$

From Bertrand's postulate, we know that $$p_{n+k+1}<2p_{n+k}<2^2p_{n+k-1}<\dots <2^k p_{n+1},$$ so that $$r(n,k)=p_n\,\frac{p_{n+1}}{p_{n+k+1}}\frac{p_{n+2}}{p_{n+k+1}}\dotsm \frac{p_{n+k-1}}{p_{n+k+1}}\frac{p_{n+k}}{p_{n+k+1}}>\frac{p_n}{2^{k+(k-1)+\dots+2+1}}=\frac{p_n}{2^{\tfrac{k(k+1)}{2}}}\xrightarrow[n\to\infty]{}+\infty $$

$\endgroup$
0
$\begingroup$

$r(n,k) \geq \frac{p_n^{k+1}}{p_{n+k+1}^k}$ and since $k$ is fixed and $n$ is approaching $+\infty$, we can assume that $k <n$, we arrive at $r(n,k) \geq \frac{p_n^{k+1}}{p_{2n}^k} = p_n (\frac{p_n}{p_{2n}})^k$

We know that $ n \ln n \leq p_n \leq 2 n \ln \frac{n}{2}$ for all $n \geq 6$.

So we get that $r(n,k) \geq p_n (\frac{n \ln n}{4n \ln n})^k = p_n \frac{1}{4^k}$

So we need to make sure that $p_n \geq 4^k$, and since $p_n \geq n$, so if $n \geq 4^k$ then $p_n \geq 4^k$ which means that $r(n,k) \geq 1$.

With the same idea $\lim \limits_{n \to \infty} r(n,k) = +\infty$, since there are infinitely many primes.

$\endgroup$
0
$\begingroup$

$r(n,k):=\dfrac {p_n...p_{n+k}}{p^k_{n+k+1}} , \forall n,k \in \mathbb N $

Taking logs, since $p_n \approx n\ln n$, $\ln(p_n) \approx \ln n + \ln\ln n$, so that

$\begin{array}\\ s(n,k) &=\ln(p_n...p_{n+k})-\ln(p^k_{n+k+1})\\ &=\sum_{j=0}^k \ln(p_{n+j})-k\ln(p_{n+k+1})\\ &\approx \sum_{j=0}^k (\ln(n+j)+\ln\ln(n+j))-k(\ln(n+k+1)+\ln\ln(n+k+1))\\ &= \sum_{j=0}^k (\ln n+\ln(1+j/n)+\ln(\ln n+\ln(1+j/n))\\ &\quad -k(\ln n+\ln(1+(k+1)/n)+\ln(\ln n+\ln(1+(k+1)/n))\\ &= (k+1)\ln n+\sum_{j=0}^k (\ln(1+j/n)+\ln \ln n+\ln(1+(\ln(1+j/n)/\ln n)\\ &\quad -k(\ln n+\ln(1+(k+1)/n)+\ln(\ln n+\ln(1+(k+1)/n))\\ &\approx (k+1)(\ln n+\ln\ln n)+\sum_{j=0}^k ((j/n)+(\ln(1+j/n)/\ln n))\\ &\quad -k(\ln n+\ln(1+(k+1)/n)+\ln\ln n+\ln(1+\ln(1+(k+1)/n))/\ln n)\\ &\approx \ln n+\ln\ln n+O(k^2/n)\\ &\quad -k(\ln(1+(k+1)/n)+(k+1)/(n\ln n))\\ &\approx \ln n+\ln\ln n+O(k^2/n) -k((k+1)/n)+(k+1)/(n\ln n))\\ &\approx \ln n+\ln\ln n+O(1/n) \qquad\text{since }k\text{ is fixed}\\ \end{array} $

Therefore the ratio diverges to $\infty$.

If the denominator has exponent $k+1$ (instead of $k$), the result is $O(1/n)\to 0$, so the ratio tends to $1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.